Enhancing Visual Literacy in 8th–9th Grade Students Through Creative Art Education - Bobomurodova Sojida Ablakulovna (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article explores methods for enhancing visual literacy in 8th–9th grade students in secondary schools. It emphasizes the importance of creative exercises, interactive teaching, and project-based learning in developing students’ compositional thinking, visual perception, and artistic skills. Implementing these approaches fosters independent thinking, creativity, and problem-solving abilities while strengthening aesthetic awareness and practical competencies.